Heralds of revolution : Russian students and the mythologies of radicalism - Morrissey, Susan K., 1963- (Oxford University Press, 1998)
Reading Russian revolutionary culture through its stories, the author of this text explores how the quest for consciousness evolved into student radicalism. The study examines the dynamics of political and cultural change in late-Imperial Russia, questioning the founding myths of the Soviet Union.